Ideology without ideologists - Lydia Mechtenberg (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2007)
Generally, Democrats do not increase military spending, and Republicans do not raise welfare payments. Mostly, ruling politicians stick to the manifesto of their party. The current paper provides a theoretical explanation for this phenomenon that does not assume politicians or voters to be ideologists. I explore an environment where both voters and politicians always prefer the policy that is adequate to the world state but contradicts the party manifesto over the policy that is in line with the manifesto but not adequate. I find that nevertheless, the inefficient manifesto-driven policy will often result from their interaction. Besides, I show that a high degree of agreement between the politician in office, his party basis and the voter makes efficient, informed policy rare or even impossible. But if homogeneity of convictions within parties is high, swing voter behavior can solve the problem.
Keywords: D72; D78; D82; 330; Information transmission; signalling; ideology; intraparty politics; political opinion; Ideologie; Politische Entscheidung; Informationsverbreitung; Wahlverhalten; Signalling; Public Choice; Theorie